Motivational Climate in Sport Is Associated with Life Stress Levels, Academic Performance and Physical Activity Engagement of Adolescents - Castro-Sánchez, Manuel (Int J Environ Res Public Health, 2019)
The present study sought to define and contrast an explanatory model incorporating motivational climate towards sport, life stress, academic performance, and engagement in physical activity, and to analyze the existing relationships between these variables as a function of sex. A total of 2452 adolescents of both sexes (42.7% males and 57.3% females) participated in the present study, with self-reported ages between 13 and 16 years (M = 14.43; SD = 1.15). Participants were from Granada (Spain) and perceived motivational climate towards sport (PMCSQ-2), life stress (PSS), academic performance, and engagement in physical activity (PAQ-A) were analyzed. A multi-group structural equation model was constructed, which demonstrated excellent fit to the observed data (χ(2) = 309.402; DF = 40; p < 0.001; CFI = 0.973; NFI = 0.970; IFI = 0.973; and RMSEA = 0.052). A negative and direct association exists between ego climate and task climate. A positive association was found between motivational climate, task climate (males r = 0.336/females r = 0.238), and ego climate (males r = 0.198/ females r = 0.089) and engagement in physical activity. A task climate was associated with better academic performance and lower levels of life stress. The main conclusions of this study highlight that a task-involving climate and engagement in physical activity are both associated with lower levels of life stress and higher levels of academic performance.